Echocardiographic Features of Chronic Chagas Heart Disease: A Prospective Study in 1038 Patients - Xavier, Sergio Salles (1999)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Rio de Janeiro, RJ, Brasil.